2004
DOI: 10.1080/00365520410003605
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress contributes to methotrexate-induced small intestinal toxicity in rats

Abstract: These results suggest that oxidative stress plays an important role in the MTX-induced small intestinal damage, especially neutrophil infiltration. Thus, the modulation of oxidative stress would be useful in reducing intestinal damage in MTX treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
87
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 137 publications
(104 citation statements)
references
References 28 publications
11
87
2
Order By: Relevance
“…Miyazano et al 14 have reported that oxidative stress may contribute to the MTX-induced small intestinal damage observed in rats, specifically as a result of ROS induced neutrophil infiltration and pro-inflammatory cytokine production. 12 normal colon weights were maintained in 5-FU damaged groups treated with GSE compared to 5-FU controls.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Miyazano et al 14 have reported that oxidative stress may contribute to the MTX-induced small intestinal damage observed in rats, specifically as a result of ROS induced neutrophil infiltration and pro-inflammatory cytokine production. 12 normal colon weights were maintained in 5-FU damaged groups treated with GSE compared to 5-FU controls.…”
Section: Discussionmentioning
confidence: 99%
“…5-FU is an anti-metabolite chemotherapy drug which blocks DNA synthesis via inhibition of thymidylate synthase 14 and is widely used for anticancer therapy. This drug often induces an inflammatory disorder known as mucositis, which is accompanied by side-effects such as nausea, bloating, vomiting, diarrhoea and gastroenteritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, low dose MTX administration has been applied to cure some autoimmune diseases such as psoriasis and rheumatoid arthritis [2]. MTX, an antimetabolite and a folic acid antagonist, can cause unpredictable serious side effects [3]. Mechanism of the side effects is not clear, yet.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanism of the side effects is not clear, yet. However, it's assumed that the main reason is related to the oxidative stress occurring during the biotransformation in liver [2][3][4].…”
Section: Introductionmentioning
confidence: 99%